Behavior of different genotypes of APIS MELLIFERA on infestation of VARROA DESTRUCTOR. - Ramos, Benjamín Gómez (2024)
Beekeeping is an agricultural activity with contributions in the economic, social and ecological sphere in Mexico. Apis mellifera bees are prone to parasites such as the Varroa destructor mite that affect the production and development of colonies. The objective of this research was determine the effect of the genotypes: Cordovan, Carniola, Caucasian and africanized Hybrid on the natural infestation and control of the parasite Varroa destructor. Twenty hives were evaluated, divided into four groups according to their genotype. Comparative measurements were taken to determine infestation percentages and to consider the damage caused to the offspring by region. The data were analyzed under generalized linear model methodology. Differences (p ≤ 0.05) were observed between genotypes for the average number of varroa/hive, Carniola and Africanized Hybrid genotypes showed sensitivity to V. destructor infestation respect to Cordovan and Caucasian. There were differences (p ≤ 0.05) between genotypes respect to damage caused by the mite. The Cordovan genotype had a level of specialization in the attack of the mite; mainly in the armor and legs. The damage was 29% caused to parasite's legs which does not allow it to remain on the bee. Likewise, this genotype had greater grooming behavior with greater specialization when mutilating the parasite. Damaging the shell and legs reduces the probability of survival. Keywords: beekeeping, beekeeping, parasite, beehives